Parenting in Egypt: Recommendations for a parenting program for upper and middle class Egyptians - Hanna, Amira Ragy Saad (AUC Knowledge Fountain, 2016)
Parenting is key for the healthy development of children. It is a complex role that requires a great deal of support. Parenting or parent education programs are good tools for supporting parents but they are not widely available in Egypt, and the ones that are available may not be culturally sensitive to the Egyptian context. In order to develop an effective parenting program, an assessment of parenting training and support needs was conducted. An online survey was administered to parents (n = 255, 47% completion rate) of children aged 0 to 12 to assess their knowledge of child development, their parenting and disciplining style, their perceptions of their strengths and struggles as parents, and their interest and needs in a parenting program. The participants exhibited some knowledge of child development with various gaps and misconceptions. Their parenting styles were inconsistent with discipline a mix of lax and harsh practices. Their saw their strengths as lying in loving and educating, and identified challenges with discipline. They also expressed interest in participating in parenting programs. Suggestions for developing parenting programs in Egypt are made based on these results. Further research is required to better understand Egyptian parenting in order to provide appropriate support for their own and their children’s wellbeing.